Can We Agree What Skilled Mindfulness-Based Teaching Looks Like? Lessons From Studying the MBI:TAC. (August 2020) - S Crane, Rebecca; Hecht, Frederick M; Brewer, Judson; Griffith, Gemma M; Hartogensis, Wendy; Koerbel, Lynn; Moran, Patricia; Sansom, Sophie; Yiangou, Alison; Kuyken, Willem
Background: The Mindfulness-Based Interventions: Teaching Assessment Criteria (MBI:TAC) is a widely used tool for assessing fidelity in mindfulness-based program (MBP) research and training. It also supports MBP teacher reflective and skill development. MBI:TAC assessors review MBP teaching and rate the teaching on 6 domains. The MBI:TAC yields individual domain and overall scores, using 6 levels of competence. Although the MBI:TAC is widely used in MBP research and training, research is at an early stage. Objective: We developed and tested a method of training MBI:TAC assessors to use the tool reliably and examined interrater reliability of the tool. Methods: A total of 31 international senior MBP teachers were recruited to join an online training to build their skills in using the MBI:TAC. The training systematically and iteratively built familiarity and skills in assessing the 6 MBI:TAC domains. Qualitative and quantitative data on trainee's experience of the training were gathered. Interrater reliability in using the tool was tested each week of the training. At the end of the training, interrater reliability was tested by asking trainees to individually assess videos that they had not previously seen. Their ratings were compared to benchmark assessments, which had been established via consensus agreement between 4 expert users of the MBI:TAC. Results: The training was well received and appreciated, with some challenges experienced in applying the assessment methodology. Participants' ratings became progressively more in line with one another and the benchmark ratings during the training. At the end, interrater reliability was high (ranging from 0.67 to 1.0). Conclusion: It is possible for senior MBP trainers, coming from different regions in the world, to align toward common understandings of the elements of MBP teaching competence and program integrity. An assessor training methodology was tested, and the learning from this project has led to refinements for future delivery.